Biofilm-forming Ability of Bacillus thuringiensis Strains from Biopesticides on Polystyrene and their Attachment on Spinach - Zhao, Xingchen; Höfte, Monica; Spanoghe, Pieter; Rajkovic, Andreja; Uyttendaele, Mieke (Journal of food protection, 2024)
•Strain-specific biofilm-forming ability was found in B. cereus group.•Nutrient-rich condition enhanced the biofilm formation of B. cereus group.•Dry formulation of B. thuringiensis enhanced their adhesion on spinach leaves.•Strength of adhesion was not improved by the formulation of B. thuringiensis. Bacillus thuringiensis-based commercial products as a biopesticide have been used for more than 60 years in agriculture. However, as one of the species in B. cereus group, B. thuringiensis has been considered as an emerging hazard with the potential to cause food toxico-infections. The present study aimed to evaluate the biofilm-forming ability of B. thuringiensis biopesticide strains and their attachment on spinach, compared to foodborne B. cereus strains. Biofilm formations of tested strains were found to be strain-specific and affected by the nutrient conditions more than the incubation time. Nutrient starvation conditions generally reduced the biofilm formation of tested B. thuringiensis and B. cereus strains, particularly B. thuringiensis ABTS-1857 strain was found as the nonbiofilm former in starvation conditions. It is worth mentioning that B. thuringiensis SA-11 strain showed stronger biofilm-forming ability with more air–liquid interface biofilm than the other two B. thuringiensis biopesticide strains, but no such higher attachment of B. thuringiensis SA-11 to spinach was observed. These results indicate that B. thuringiensis SA-11 strain can enter the food processing lines by the attachment on spinach leaves, and it has the potential to form biofilms throughout the processing lines or the production environment when sufficient nutrients are available. However, more biofilm tests of B. thuringiensis biopesticide strains in the vegetable production chain should be performed. The dry formulation of commercial B. thuringiensis biopesticides enhanced their adhesion on spinach leaves, whereas the strength of adhesion was not improved by the formulation. In addition, 1–2 log reductions of spores after the intensive washing of spinach leaves in the lab were detected. However, the log reduction due to the actual washing done by the food processing companies in large-volume washing baths or by consumers at home would be limited and less than this lab simulation.